Breast location of tuberculosis: a case report and literature review - Mian, Dehi Boston; Loue, Vedi Andre Serges; Angoi, Aya Virginie; Yao, Alexis; Kouyate, Mohamed; N' guessan, Koffi; Boni, Serge (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Breast tuberculosis (TB) is a rare localization of extra-pulmonary TB. We report the first case observed in our daily activities to show the difficulties in the diagnosis and the good evolution in the treatment. In spite of the fact that it is rare, breast TB should not be ignored, especially in a country with high TB endemicity.